A Case of Immunoglobulin G4-Related Disease with Extensive Multiorgan Involvements - Kazuhiko Higashioka; Kenji Yoshida; Kensuke Oryoji; Kazuo Kamada; Shinichi Mizuki; Hiroshi Tsukamoto; Eisuke Yokota; Koichi Akashi (Case Reports in Rheumatology)
We report a case of IgG4-related disease (IgG4-RD) with multiple ten-organ involvement. This case showed many clinical findings, such as bilateral swelling of salivary and lacrimal glands, autoimmune pancreatitis, interstitial nephritis, retroperitoneal fibrosis, periaortitis, systemic swelling of lymph nodes, pulmonary lesions, splenomegaly, and jejunal lesions. He was suspected as having SLE or malignant lymphoma but diagnosed as having IgG4-RD by the elevated serum IgG4 level and histological findings from kidney and lymph node. We report a case of IgG4-RD with multiple ten-organ involvement that was successfully treated with prednisolone therapy.